LEADERSHIP STYLES AND PRACTICES OF SCHOOL HEADS ON TEACHERS’ TEACHING ACCOMPLISHMENT - Olasiman, Ma. Rizza; Torreon, Leandro C. (International Journal of Research -GRANTHAALAYAH, 2024)
It has been known that leadership is vital in any organization and institution. The school heads leadership styles and practices and teachers teaching accomplishment are interconnected. The purpose of this study was to assess the level of school heads leadership styles and practices and its effectiveness on teacher’s teaching accomplishments. There was a total of five hundred ninety-eight (598) respondents who were the ninety-eight school heads and five hundred teachers, identified respondents to participate in the study. The researchers utilized the descriptive-survey design employing the simple random sampling technique with the use of a modified research tool from the study of Abwalla Jay “The Principal’s Leadership Styles and Teachers Performance” (2014) and Stellarleadership.com for the school heads leadership styles. A survey tool anchored from National adoption and Implementation of the Philippine Professional Standards for School heads (DepEd Order No. 24 s. 2020) for school heads leadership practices and for teacher’s teaching accomplishment the Result-Based Performance System (RPMS) was used. The result revealed that there is no significant relationship between the school heads’ leadership styles and their profile in terms of age, sex, experience, educational attainment, and position or designation. Further, there is sufficient evidence of significant correlation between the leadership styles of school heads and the accomplishments of teachers. Likewise, there is sufficient evidence of significant correlation between the school heads’ leadership styles and teachers’ accomplishments. This study concludes that the school heads’ leadership styles were not influenced by the school heads’ age, sex, experience, educational attainment, and position or designation.